PELATIHAN KEMAMPUAN E-LEARNING GURU MATEMATIKA DENGAN MENGGUNAKAN MOODLE - Syariful Fahmi; Soffi Widyanesti Priwantoro; Burhanudin Arif Nur Nugroho (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2018)
ABSTRACTThe ability of teachers to teach influenced by ability in technology in the learning process. E-learning as one form of technology will help teachers in the process of teaching and learning. Therefore the ability of e-learning mastery teachers becomes key words in the activities of e-learning in education. One form of E-learning is moodle. The purpose of this training is to provide skills for teachers of mathematics in developing media-based learning, moodle. Moodle is an application program that can modify a media learning into web forms. This application allows students to enter into the "digital classroom" to access learning materials. The participants of these activities is the mathematics teacher of SMP Muhammadiyah 1 Godean, SMP Muhammadiyah 1 Minggir, SMP Muhammadiyah 1 Gamping, SMP Muhammadiyah 1 Moyudan, SMP Muhamamdiyah 1 Depok and SMP Muhammadiyah 2 Depok. The method of training is giving lectures about moodle, the practice and accompaniment the creation of media-based learning, moodle. This training has managed to build the learning system with the concept of e-learning (electronic learning) or distance learning (distance learning). With this concept the system of teaching and learning will not be limited to space and time. A teacher can give a lecture learning materials from anywhere. Similarly, a student can follow lectures from anywhere.Keywords: E-Learning MoodleABSTRAKKemampuan mengajar guru salah satunya dipengaruhi oleh kemampuan penggunaan teknologi dalam proses pembelajaran di kelas. E-learning sebagai salah satu bentuk teknologi akan membantu guru dalam proses belajar mengajar. Oleh karena itu kemampuan penguasaan e-learning guru menjadi kata kunci dalam kegiatan e-learning dalam pendidikan. Salah satu bentuk E-learning adalah dengan menggunakan moodle. Tujuan dari pelatihan ini adalah memberikan ketrampilan bagi guru-guru matematika dalam mengembangkan media pembelajaran berbasis moodle. Moodle merupakan program aplikasi yang dapat merubah sebuah media pembelajaran kedalam bentuk web. Aplikasi ini memungkinkan siswa untuk masuk kedalam â€œruang kelas digitalâ€ untuk mengakses materi-materi pembelajaran. Peserta kegiatan ini adalah para guru matematika dari SMP Muhammadiyah 1 Godean, SMP Muhammadiyah 1 Minggir, SMP Muhammadiyah 1 Gamping, SMP Muhammadiyah 1 Moyudan, SMP Muhamamdiyah 1 Depok dan SMP Muhammadiyah 2 Depok. Metode pelatihan adalah dengan ceramah tentang moodle, praktek secara langsung dan pendampingan pembuatan media pembelajaran berbasis moodle. Pelatihan ini telah berhasil membangun sistem pembelajaran dengan konsep e-learning (pembelajaran secara elektronik) ataupun distance learning (pembelajaran jarak jauh). Dengan konsep ini sistem belajar mengajar akan tidak terbatas ruang dan waktu. Seorang guru dapat memberikan materi pembelajaran kuliah dari mana saja. Begitu jugaKata Kunci: E-Learning Moodle